POSISI DPRD DALAM UU NO. 32 TAHUN 2004 - FITRIYAH, FITRIYAH (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
AbstractLaw No. 22/1999 on local governance gives more power to Local Assemblies (DPRD) as